1998
DOI: 10.1073/pnas.95.5.2680
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids suppress voltage-gated Na + currents in HEK293t cells transfected with the α-subunit of the human cardiac Na + channel

Abstract: Studies have shown that fish oils, containing n-3 fatty acids, have protective effects against ischemiainduced, fatal cardiac arrhythmias in animals and perhaps in humans. In this study we used the whole-cell voltage-clamp technique to assess the effects of dietary, free long-chain fatty acids on the Na ؉ current (I Na,␣ ) in human embryonic kidney (HEK293t) cells transfected with the ␣-subunit of the human cardiac Na ؉ channel (hH1 ␣ ). Extracellular application of 0.01 to 30 M eicosapentaenoic acid (EPA, C20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 34 publications
4
105
1
1
Order By: Relevance
“…In the domain of stroke disorders, there is growing evidence that the omega-3 precursor, ALA, is a potent protector in several models of global and focal ischemia (Xiao et al, 1998;Lauritzen et al, 2000;Blondeau et al, 2001Blondeau et al, , 2002Blondeau et al, , 2007Lang-Lazdunski et al, 2003;Heurteaux et al, 2004Heurteaux et al, , 2006a. In a mouse model of stroke, we found that a single injection of ALA, after the onset of stroke, significantly reduced infarct size and improved the neurological score 24-h post-ischemia.…”
Section: Introductionmentioning
confidence: 70%
“…In the domain of stroke disorders, there is growing evidence that the omega-3 precursor, ALA, is a potent protector in several models of global and focal ischemia (Xiao et al, 1998;Lauritzen et al, 2000;Blondeau et al, 2001Blondeau et al, , 2002Blondeau et al, , 2007Lang-Lazdunski et al, 2003;Heurteaux et al, 2004Heurteaux et al, , 2006a. In a mouse model of stroke, we found that a single injection of ALA, after the onset of stroke, significantly reduced infarct size and improved the neurological score 24-h post-ischemia.…”
Section: Introductionmentioning
confidence: 70%
“…Concentrations of ethanol used for dissolving fatty acids were negligible and had no effect on Na ϩ currents in HEK293t cells. Currents were acquired and analyzed as before (3,5). Experiments were conducted at 22-23°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data demonstrated that PUFAs significantly shifted the steady-state inactivation of cardiac Na ϩ currents to more hyperpolarized values (3,5,6). To test whether single point mutations altered the EPA-induced shift of the steady-state inactivation, we investigated the effects of different concentrations of EPA on inactivation of the wild type and its three mutants of hH1 ␣ Na ϩ channels.…”
Section: Reduction Of Epa-induced Hyperpolarizing Shift Of Ina Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the knowledge concerning the anti-inflammatory effects of x-3 PUFAs on the myocardium is limited to a potent anti-arrhythmic action that has been described both in vivo on myocardium [38,40] and in vitro on cardiomyocytes [26,31]. The presence of PUFAs in cardiomyocyte membrane phospholipids modulates Na + , K + and Ca 2+ channels' activity [62,63] causing an electric stabilization of cells and thus prevention of arrhythmias.…”
mentioning
confidence: 99%